2016
DOI: 10.15403/jgld.2014.1121.251.hpe
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Virus in Autoimmune Hepatitis Patients in the Netherlands

Abstract: Background & Aims: In recent years chronic courses of hepatitis E virus (HEV) infection have been described in immunosuppressed individuals. This may implicate a potential role for HEV in the development of autoimmune diseases, including autoimmune hepatitis (AIH). Here we investigated the prevalence of HEV-antibodies in AIH patients in an endemic Central European country. Methods: HEV-specific immunoglobulin G (IgG) and HEV RNA were determined in 354 and 377 AIH patients, respectively. Clinical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
(33 reference statements)
4
28
0
2
Order By: Relevance
“…However, these results could not be reproduced in a cohort of AIH patients from the Netherlands [15], where the incidence of HEV is particularly high [16]. HEV IgG seroprevalence in both AIH and blood donors was around 27% [15].…”
Section: Introductionmentioning
confidence: 83%
“…However, these results could not be reproduced in a cohort of AIH patients from the Netherlands [15], where the incidence of HEV is particularly high [16]. HEV IgG seroprevalence in both AIH and blood donors was around 27% [15].…”
Section: Introductionmentioning
confidence: 83%
“…Recently, a German and an Austrian study supported this hypothesis by showing a higher anti‐HEV IgG prevalence in AIH patients compared to that in the general population 12,13 . However, a larger Dutch study showed no significant difference in the anti‐HEV prevalence between AIH patients and the general population; thus, this association remains controversial 14 . The anti‐HEV IgG prevalence among the general population in South Korea has been reported variously from 9% to 34%; however, the nationwide number of confirmed diagnostic code of acute hepatitis E is about 60 cases according to National Health Insurance Claims Data (Korea National Institute of Health inner data).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to exclude other causes of hepatitis and evaluate treatment compliance before definitively diagnosing these patients with "difficult-to-manage" AIH. [40][41][42][43][44][45] AIH is an immune-mediated liver disease, thus biological agents, such as infliximab (anti-tumour necrosis factor [TNF] therapy), rituximab (anti-B cell therapy) or even tocilizumab (anti-IL-6 therapy) may have a potential role as disease-modifying agents and salvage therapies. 17,46,47 Anti-TNF treatment (infliximab) has been applied successfully as a rescue therapy in AIH.…”
Section: Discussionmentioning
confidence: 99%